Effect of buckwheat processing products on dough and bread quality made from whole-wheat flour - Drobot, Vira; Semenova, Anastasia; Smirnova, Elizabeth; Mykhonik, Larysa (My University, 2014)
The article gives a brief overview of the current nutritional situation of the Ukrainian population and describes useful buckwheat properties. The objective of the paper is to study the effect of buckwheat processing products (flour and flakes) on the technological process and quality of bread made from whole-wheat flour. This article describes and analyzes research data on the rheological properties of dough samples which were determined by farinograph and amylograph.
Keywords: buckwheat; processing products; dough; whole-wheat flour; rheological properties; гречка; продукти переробки; тісто; борошно з суцільнозмеленого зерна пшениці; реологічні властивості; кафедра технології хлібопекарських і кондитерських виробів; продукты переработки; тесто; мука из цельноперемолотого зерна пшеници; реологические свойства; кафедра іноземних мов професійного спрямування